Efficient Coil Design by Electromagnetic Topology Optimization for Electromagnetic Sharp Edge Forming of DP980 Steel Sheet - Choi, M. K.; Huh, H.; Seo, M. H.; Kang, Y. (Technische Universität Dortmund, 2016)
This paper proposes a design method of the tool coil by topology optimization for the electromagnetic sharp edge forming process. Topology optimization is an approach that optimizes material configuration in a given domain to meet the design requirements. The design problem for the tool coil is defined as enhancing efficiency of the forming process and optimization problem is set to be maximization of the Lorentz force induced on the tool coil. A new topology optimization formulation based on the numerical methods for electromagnetism using FEM and BEM is developed for maximization of the Lorentz force. Optimum design of the tool coil is obtained by the topology optimization using the element density approach. The optimized result is compared with other coils which have different configurations to show the effectiveness of the proposed method. The idea of applying topology optimization to the design of the tool coil is successful and this formulation deals effectively for the optimization problems.
Keywords: coil design; electromagnetic sharp edge forming; topology optimization; 620; 670; Magnetumformen; Finite-Elemente-Methode